2019
DOI: 10.1103/physrevx.9.041019
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Neutral Optical Excitations Using Electric Fields

Abstract: Mobile quantum impurities interacting with a fermionic bath form quasiparticles known as Fermi polarons. We demonstrate that a force applied to the bath particles can generate a drag force of similar magnitude acting on the impurities, realizing a novel, nonperturbative Coulomb drag effect. To prove this, we calculate the fully self-consistent, frequency-dependent transconductivity at zero temperature in the Baym-Kadanoff conserving approximation. We apply our theory to excitons and exciton polaritons interact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 67 publications
2
30
0
Order By: Relevance
“…which agrees with previous calculations using Green's functions [48]. This matrix element describes the amplitude for the emission of an electron-hole pair with momenta k and q by a polaron of momentum p. We emphasize that the above matrix element can also describe the residual interaction between the upper polaron-polariton and the Fermi sea, if we replace the coefficients ϕ and energy E p with the corresponding values for the upper polaron-polariton.…”
Section: Polaron-electron Interactionsupporting
confidence: 88%
“…which agrees with previous calculations using Green's functions [48]. This matrix element describes the amplitude for the emission of an electron-hole pair with momenta k and q by a polaron of momentum p. We emphasize that the above matrix element can also describe the residual interaction between the upper polaron-polariton and the Fermi sea, if we replace the coefficients ϕ and energy E p with the corresponding values for the upper polaron-polariton.…”
Section: Polaron-electron Interactionsupporting
confidence: 88%
“…The many-body polaronic states are expected to be charge neutral [31,32], suggesting the absence of coupling to external fields. In a recent theoretical study however, it was shown that neutral polarons are sensitive to the average force on electrons, leading to a finite polaron transconductivity in the non-equilibrium limit -an effect that is observable even when polarons hybridize with cavity photons [35].In the present work, we demonstrate experimentally that external electric and magnetic fields effect forces on polaron-polaritons. In contrast to earlier proposals, we find that the observed polariton acceleration primarily originates from a source-drain voltage induced density gradient in the two dimensional electron gas (2DEG) in which polaritons are immersed.…”
supporting
confidence: 50%
“…By mapping the energy landscape of the lower polariton, we reach quantitative agreement between a simple trajectory based model and the observed polariton acceleration. Our experiment constitutes an alternative to the already proposed polariton drag effect for effecting electro-magnetic forces on neutral optical excitations [18,35]. We emphasize that the electron density gradients we exploit are generic for low density 2DEGs when large source-drain voltages are applied and therefore need to be considered in view of polariton drag experiments.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…More specifically, using time resolved four-wave mixing (FWM) experiments [28,29], we find that polariton-polariton interactions U can be enhanced by more than an order of magnitude around the fractional state at filling factor ν = 2/5 as compared to other neighboring compressible states. The interplay between photonic excitations and a 2DES is an exciting field [30][31][32][33][34] with open problems, among others, concerning the relation between transport and optics [35][36][37] and the description of exciton-electron interactions in a magnetic field [10].We study a semiconductor heterostructure that features, at the center of an optical microcavity, a GaAs QW containing an electron system of density n e = 3 × 10 10 cm −2 (see Methods). In the presence of a 2DES, electronexciton interactions modify the excitation spectrum and pioneering studies showed the existence of the strong coupling regime [38,39].…”
mentioning
confidence: 99%